SMALL NEW MEMBER STATES IN THE EU FOREIGN POLICY: TOWARD ‘SMALL STATE SMART STRATEGY’? - Pastore, Gunta (Baltic Journal of Political Science, 2013)
This article explores the small new member states at the EU ‘frontline’ in their efforts to upload their geographic preferences in the EU foreign policy. It starts by reviewing the preferences of Cyprus, Estonia, Latvia, Lithuania, Malta, and Slovenia. Next, it compares how they pursued these preferences in the EU. Third, it indicates their uploading success. Finally, it notes that these countries, despite their ‘double disadvantages’1, moved closer toward ‘small state smart strategy’2, including compromise-seeking behaviour, persuasive deliberation, lobbying, and using coalitions. While their uploading success has been mixed, their preference projection in the EU foreign policy has been visible.